Saving Face and Group Identity - Tor Eriksson; Lei Mao; Marie Claire Villeval (Institute for the Study of Labor (IZA), 2015)
Are people willing to sacrifice resources to save one's and others' face? In a laboratory experiment, we study whether individuals forego resources to avoid the public exposure of the least performer in their group. We show that a majority of individuals are willing to pay to preserve not only their self- but also other group members' image. This behavior is frequent even in the absence of group identity. When group identity is more salient, individuals help regardless of whether the least performer is an in-group or an out-group. This suggests that saving others' face is a strong social norm.
Keywords: C92; D03; M52; Z13; 330; pro-social behavior; social image; saving face; group identity; experiment